Welcome to Finnish Literature! Hassan Blasim and the Politics of Belonging - Löytty Olli (Finland, 2022)
The article discusses Hassan Blasim’s precarious position in the Finnish literary field. Blasim is an Iraqi-born author who came as a refugee to Finland in 2004. Since then, he has become an internationally acclaimed author whose short stories, written in Arabic, have been translated into more than 20 languages, including Finnish. However, his inclusion in the Finnish literary field is questionable: while he has gained increasing recognition in the form of awards and grants, he cannot join, due to the original language of his work, either the national writers’ union for Finnish speakers or its Swedish-language counterpart. Blasim’s status as an immigrant makes him a stranger in Finland, part insider and part outsider. The article elaborates on the sociological concept of "stranger", as explicated by Georg Simmel, in reference to writers like Blasim. It also examines the media reception of Blasim and his books in Finland. The analysed material consists of journalistic texts on Blasim as well as his books published in Finnish newspapers and magazines from 2009 to 2014, from the first articles about him in the Finnish media to the news of him receiving the Independent Foreign Fiction Prize.